Adaptive instantaneous frequency estimation of noisy nonstationary signals : doctoral thesis - Lerga, Jonatan; Seršić, Damir; Sučić, Viktor (Zagreb : J. Lerga ; Fakultet elektrotehnike i računarstva, 2011)
ABSTRACT: Methods for a noisy nonstationary signal instantaneous frequency (IF) estimation from its time-frequency representation (TFR) have been proposed. The IF estimation error exhibits bias and variance dependant on the TFR analysis window width. Due to the opposite tendency of bias and variance with respect to the lag window width, a proper width has been found as the one providing the bias-to-variance tradeoff that reduces the estimation error. The adaptive window widths have been obtained by the improved intersection of confidence intervals (ICI) rule, proposed in the thesis. In the case of multicomponent signals, the components IF estimation was preceded by their localization and extraction from the signal TFR using the modified adaptive algorithm proposed in this thesis. The IF estimation has resulted in error reduction by up to 73% for monocomponent signals and by up to 23% for multicomponent signals in terms of the mean squared error when compared to the original ICI-based method. It has been also shown that the estimates are significantly less sensitive to the initial window widths set selection. Furthermore, the highest improvement in the IF estimation accuracy was achieved in high noise environments, for which many of the existing methods are known to fail. - KEYWORDS: Instantaneous frequency estimation, time-frequency representation, nonstationary signals, monocomponent signals, multicomponent signals, components extraction, adaptive lag window width, relative intersection of confidence intervals (RICI) rule, improved intersection of confidence intervals (ICI) rule
Na spor. nasl. str.: Adaptivna procjena trenutne frekvencije zašumljenih nestacionarnih signala : doktorska disertacija. - This Ph. D. thesis was accomplished at the University of Zagreb, Faculty of Elelctrical Engineering and COmputing, Department of Electronic Systems and Information Processing
Bibliografija: str. 63-72. - Sažetak na hrv. i eng. - Kazalo oznaka: str. 13-16. Kazalo kratica: str. 17. - Kazalo autorovih objavljenih radova: str. 11-12.